2006
DOI: 10.1002/dc.20500
|View full text |Cite
|
Sign up to set email alerts
|

Extra-salivary gland presentations of adenoid cystic carcinoma: A report of three cases

Abstract: Adenoid cystic carcinoma (ACC) is a malignant neoplasm most commonly originating in salivary glands of the head and neck area. When ACC presents outside of these locations, the diagnosis may become more challenging. We describe three cases of ACC presenting in extra-salivary gland sites. Two cases were metastatic; in case 1 the initial presentation was widespread bony metastasis of unknown primary origin. The other metastatic case (case 2) was from a patient presenting with a pleural effusion and a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…ACC arises at sites where seromucinous or sweat gland epithelium is present and commonly affects the submandibular and minor salivary glands. Rarely can it occur at extra‐salivary locales like lacrimal glands, nasopharynx, maxillary antrum, tongue, larynx, tracheo‐bronchial tree, lung, breast, uterine cervix, ovary, Bartholin glands, oesophagus, prostate, external ear, and skin …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACC arises at sites where seromucinous or sweat gland epithelium is present and commonly affects the submandibular and minor salivary glands. Rarely can it occur at extra‐salivary locales like lacrimal glands, nasopharynx, maxillary antrum, tongue, larynx, tracheo‐bronchial tree, lung, breast, uterine cervix, ovary, Bartholin glands, oesophagus, prostate, external ear, and skin …”
Section: Introductionmentioning
confidence: 99%
“…Lungs are the most common site for distant metastasis followed by bone. Less frequently, metastasis can involve liver, skin, optic disc, choroid, brain, spine, and kidney …”
Section: Introductionmentioning
confidence: 99%
“…All of these features that recapitulate the histopathology of AdCC are helpful in correctly orienting the cytological diagnosis of this neoplasm. Sometimes, isolated hyaline globules can be observed (7, 20, 24, 26); singly dispersed cells are present on some smears (11, 26). The basement membrane material, forming globules that have a light blue appearance on PAP stain and bright magenta on MGG stain, is the characteristic feature of AdCC; diagnostic difficulties arise when they are not present on cytological material, as the pattern could mimic carcinoid tumor, SCLC, NSCLC, and reserve cell hyperplasia (19).…”
Section: Discussionmentioning
confidence: 99%
“…Florentine et al (25) reported a patient who had metastatic bone disease from unknown primary as the initial diagnosis, and the patient's further medical history showed a record of early-stage adenoid cystic carcinoma (ACC) of the soft palate, which had been diagnosed and resected 3 months earlier. The bone histopathology was compatible with ACC.…”
Section: Discussionmentioning
confidence: 99%